2023
DOI: 10.1007/s10942-023-00497-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rational Emotive Behaviour Therapy (REBT) Group Counselling Program on Competitive Anxiety of Student-Athletes

Abstract: Aim:The purpose of this study was to develop a Rational Emotive Behaviour Therapy (REBT) based group counselling program for athletes, and then to experimentally test the effects of the program on the competitive anxiety and irrational beliefs of non-western student-athletes. Methods:The effects of the REBT based program was examined using a 2 x 2 controlled quasiexperimental group design. 22 student-athletes participated in the study (11 in the experimental group and 11 in the control group). The Sport Anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
0
3
0
1
Order By: Relevance
“…Mixed methods studies (n = 2) . Two studies [ 109 , 110 ] reported significant reductions in irrational beliefs from pre- to post-intervention with large effect sizes. One study also reported significant increases in rational beliefs (large effect size) and noted that changes were maintained at follow-up [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mixed methods studies (n = 2) . Two studies [ 109 , 110 ] reported significant reductions in irrational beliefs from pre- to post-intervention with large effect sizes. One study also reported significant increases in rational beliefs (large effect size) and noted that changes were maintained at follow-up [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Group counselling is a method that has been proven effective in helping individuals overcome psychological problems and improve their mental well-being (Prabowo, 2020;Utamy et al, 2021;Wulandari, 2020). Meanwhile, cognitive reconstruction techniques are a cognitive-behavioural approach that has proven effective in changing negative thought patterns into positive ones and helping individuals respond to situations more adaptively (Kara et al, 2023;Seligman & Reichenberg, 2010;Short & Thomas, 2015). When these two approaches are combined into hybrid group guidance with cognitive reconstruction techniques, the potential for achieving more optimal results in developing individual cognition and behaviour becomes even more significant (Cruvinel et al, 2019;Phuntsho & Gonsalves, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Atıf: Kara, E., (2023). Tekrarlanabilirlik krizi ve geçerlilik krizi kıskacındaki psikoloji ve sosyal bilimlerde krizden çıkış için öne çıkan iki trend: "Yeni İstatistik" ve "Bayesyen İstatistik".…”
Section: öZunclassified